Supporting Factors for Community Participation in the Waste Bank Program: A Study in Sleman Regency of Indonesia - Reni Dwi Astuti; Utaminingsih Linarti; Dicky Matura Sa'ban (Jurnal Optimasi Sistem Industri, 2021)
The waste bank is one of the methods used by the Government of Sleman Regency, DIY, to solve the waste problem. However, citizen participation to be active as customers in the waste bank is still lacking. For this reason, a study was conducted to find out what factors affect the level of activity of citizens in depositing waste into the waste bank. The research uses The Theory of Planned Behavior, coupled with factors: knowledge of how and what and knowledge of consequences. Data was collected through interviews with several bank administrators and customers and filling out the questionnaire. Respondents were selected by purposive sampling from 11 waste banks. The analysis method uses multiple linear regression by testing the significance of the regression model, the coefficient of determination, and the partial effect test of each variable. The results showed that attitudes, subjective norms, contr, knowledge of how and what, and knowledge of consequences simultaneously affected 73% of the intention. Among the five independent variables, only the perceived behavioral control has no partial effect. The study also showed that the intention had a significant effect on the waste bank's active behavior with a coefficient of determination of 63%.